Contextualising the Ongoing 'Southern Cameroons' Crisis within the Framework of the Right to Self-Determination. Issue 2 (May 2022) - Ashukem, Jean-Claude N.
Abstract : Incontestably the right to self-determination is useful in ascertaining which entities have and are entitled to the privileges of statehood and territorial control. Yet certain fundamental questions require clarification, questions such as: what are the special characteristics of some minority groups and what is there about their quests for independence that would justify their being permitted to secede; when and under what circumstances does the right to external self-determination accrue; what is the role of the great power theory in the framework of self-determination and to what extent does the role of the great powers promote or hinder claims for self-determination. This article answers these thought-provoking questions by situating the ongoing Southern Cameroon crisis in the context of the right to self-determination. It provides an analysis of self-determination in relevant international and African regional human rights instruments and distils standards to determine the legitimacy and legality of Southern Cameroon's quest for self-government. It argues that Southern Cameroons meet the standards for self-determination and deserves autonomy and statehood, and that any peaceful resolution of the crisis should hinge on the respect and implementation of Southern Cameroons' right to self-determination.